Insights from 25 years of oncogenetics: one person’s perspective - Friedman, Eitan (Frontiers in Genetics, 2023)
"Oncogeneticist? Never heard of this. What kind of a specialty is this?" "Why do I need to know my cancer risk? This is TMI. You are going to cause women to be depressed and even commit suicide" " I am an oncologist. I can provide all the information on genetics and cancer risk to all my patients. No need for oncogenetic counseling". This is just a short and non-representative list of some of the comments and responses that I have been getting in early 1995 when the oncogenetics service at the Genetics institute, Sheba Medical Center in Israel was established. The purpose of this article is to describe the key points and issues that were raised throughout my personal journey since then. During that time, oncogenetics was transformed from a rare oddity to a pivotal player and a successful example of implementing personalized preventive medicine by identifying and providing care and offering means for early detection and risk reduction for adults who are genetically predisposed to developing a potentially life-threatening diseases- cancer in this case